2021
DOI: 10.1111/jce.15036
|View full text |Cite
|
Sign up to set email alerts
|

Focal impulse and rotor modulation guided ablation versus pulmonary vein isolation for atrial fibrillation: A meta‐analysis of head‐to‐head comparative studies

Abstract: Introduction Empirical pulmonary vein isolation (PVI) remains the cornerstone for catheter ablation of atrial fibrillation (AF). Various ablation strategies and modalities are continually tested with the aim of improving ablation outcomes. Although focal impulse and rotor modulation (FIRM)‐guided ablation is currently used as an adjunct to PVI, evidence supporting this strategy is conflicting. We sought to examine whether the utilization of FIRM‐guided ablation with or without PVI is associated with a decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 19 publications
2
12
0
1
Order By: Relevance
“…Consequently, these ROIs should potentially be eliminated in addition to PVI. A comparable effect of focal sources was reported previously [10,14,15]. In contrast to focal ROIs, rotational findings from CARTOFINDER mapping were not reproducible during remapping.…”
Section: Benefits Of Cartofinder Mapping In Persistent Afsupporting
confidence: 83%
“…Consequently, these ROIs should potentially be eliminated in addition to PVI. A comparable effect of focal sources was reported previously [10,14,15]. In contrast to focal ROIs, rotational findings from CARTOFINDER mapping were not reproducible during remapping.…”
Section: Benefits Of Cartofinder Mapping In Persistent Afsupporting
confidence: 83%
“…Although the CONFIRM (Conventional Ablation for Atrial Fibrillation With or Without Focal Impulse and Rotor Modulation) study reported a high degree of freedom from AF with FIRM ( 42), other studies have demonstrated that, despite the association with a more organized fibrillatory activation within the LA, it does not correlate with an increase in freedom from AF, even after redo procedures (43)(44)(45)(46). Furthermore, a head-to-head meta-analysis of six studies including 716 patients (88.5% non-PAF) concluded that FIRM did not add any benefit in improving all-atrial arrhythmia recurrence (47). (Figure 5)…”
Section: Rotorsmentioning
confidence: 99%
“…25 A follow up study showed that FIRM-guided ablations prevented early and late arrhythmia recurrence for more than three years (compared to one year for PVI-only). 26 However, further studies have not been able to demonstrate the efficacy of reentrant driver ablation using FIRM, 27 , 28 which could potentially be attributed to the low resolution of the basket catheter. 29 …”
Section: Breakthrough Clinical Advancements In Our Understanding Of Afmentioning
confidence: 99%